PENGARUH BUDAYA ORGANISASI, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI UNIVERSITAS RIAU KEPULAUAN - MAGNETA HISYAM (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study analyzes the influence of the culture of the Organization, competence and discipline work against the performance of employees. This research was conducted with the approach of the survey and interview respondents characteristic Description and research data using descriptive analysis. Population research used was a clerk in the University of Riau Islands, i.e. as many as109 people. The techniques used in determine the samples is to use the census method, hypothesis testing in this study using a t-test statistics to know the influence ofpartial research, statistical Test f (simultaneously) and auto correlation to find out the results of the study the most dominant effect, with the help of the program SPSS 21.0 for Windows. Based on the results of the study showed that the test result f (Simultaneous) indicate a variable cultural organizations, competence and discipline working together is positive and significant effect on performance clerk University of Riau Islands. The results of the regression analysis in partial (t-test) shows that the culture of the Organization, competence and work discipline has a significant and positive influence on performance clerk University of Riau Islands. And organizational culture is most dominant in the variables that influence employee performance against the University of Riau Islands.